56.3k views
2 votes
Simplify.

(-3ab^3)^4

A. -7ab^12
B. -12a^4b^7
C. -81a^4b^7
D. 81a^4b^12

User PTQuoc
by
5.3k points

1 Answer

5 votes

Answer:

D

Explanation:

Use main properties of powers:

1.
(a\cdot b)^m=a^m\cdot b^m;

2.
(a^m)^n=a^(mn).

Thus,


(-3ab^3)^4=(-3)^4\cdot a^4\cdot (b^3)^4.

Hence,


(-3)^4=81,\\ \\(b^3)^4=b^(3\cdot 4)=b^(12),

then


(-3ab^3)^4=(-3)^4\cdot a^4\cdot (b^3)^4=81a^4b^(12).

User Gregsparrow
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.